INDISPENSABLE GLOBAL ROLE OF ENGLISH LANGUAGE FOR SUSTENANCE OF SUSTAINABLE DEVELOPMENT GOALS: NIGERIA IN PERSPECTIVE - Eneh-Onyejeli, Uche Ethel (EBSU Journal of Social Sciences and Humanities, 2025)
Throughout human history, the primacy of language has never been in doubt. A language achieves genuine global status when its use for communication has special effects recognized universally. Today, it is almost impossible to escape the global influence of the English language. Its importance as a means of communication is incalculable and indispensable. By the 21st century, English has been widely accepted and is used as a common language for communication, making the world more interconnected and accessible. This paper explores the reasons why learning English is essential, its role in global sustainable development goals, and how it sustains these goals, using Nigeria as a case study. Key terminologies framing the research are discussed in relation to the topic. The paper links the essential reasons for learning English to its role in achieving development goals, establishing the language’s prime influence worldwide through common global communication. Recommendations are provided on how to sustain English communication to ensure its role in supporting sustainable development goals, particularly in Nigeria and globally.